ANALISIS KESESUAIAN LAHAN UNTUK PENGEMBANGAN KOMODITI PERKEBUNAN POTENSIAL DI KECAMATAN LEITIMUR SELATAN KOTA AMBON - Robby G Risamasu (JURNAL BUDIDAYA PERTANIAN, 2016)
Assessment of chemical properties for 6 soil samples for its fertility in the study area was as follows: Soil pH ranged from acid to slightly acid (5.0-6.0), C-organic low to very high (0.64-7.9%), N-total very low to low (0.09-0.25%), P-available (Bray I) very low to low (0.0-12.4 ppm), very low to moderate Ca (0.0-8.9 me/100 g), very low to high Mg (0.2-4.9 me/100 g), very low to moderate K (0.0-0.3 me/100 g), very low to low Na (0.0-0.1 me/100 g), low CEC (2.7-13.7 me/100 g), very low to very high base saturation BS (5.6-78.9%). The soil fertility status at the study sites only used CEC parameters (cmol/kg), BS (%), organic matter (%) and P2O5 ppm. Soil fertility status in the study area ranged from very low (SR), low (R), to moderate (S). Based on the assessment of the land suitability class on the four plantations of coconut, cocoa, cloves and nutmeg, it can be seen that the plantation commodity group which was considered to have the S3 land suitability class (as marginal) is 4.146 Ha or 86.7%, and N (not suitable) accordingly was an area of ​​636 Ha or 13.3%. With soil physical limiting factors: Rooting medium (rc): Soil depth, - Danger of erosion (eh): Slope. Limiting Factor of Agroclimatology/climate (wa): Rainfall, Nutrient Availability (na): N, P, K.